Ni ion damage structures and hardness changes in austenitic stainless steels and their model alloys. (January 2016) - Sato, K; Ishioka, S.; Xu, Q; Yoshiie, T; Tsuchida, H; Itoh, A
Abstract: Defect structures of austenitic stainless steels and their model alloys after 6 MeV Ni ion irradiation were studied using positron annihilation lifetime measurements and Vickers hardness obtained from micro-hardness measurements. After irradiation at room temperature, a long lifetime of 150-180 ps was obtained and the Vickers hardness increased with increasing the irradiation dose. After irradiation at 573 K, all the alloys exhibited lifetime spectra that were not decomposed into two components. Their hardness also increased with the irradiation dose, but the enhancement was small compared with that at room temperature. Defects introduced by the ion irradiation could be detected near the surface using a Na-22 source. The hardness is correlated with the density and size of the defect clusters.